Extramedullary Hematopoiesis (EMH) in Laboratory Animals: Offering an Insight into Stem Cell Research. Issue 3 (March 2015) - Chiu, Shao-Chih; Liu, Hua-Hsing; Chen, Chia-Ling; Chen, Pin-Ru; Liu, Ming-Chao; Lin, Shinn-Zong; Chang, Ko-Tung
Extramedullary hematopoiesis (EMH) is a pathological process secondary to underlying bone marrow (BM) insufficiency in adults. It is characterized by the emergence of multipotent hematopoietic progenitors scattered around the affected tissue, most likely in the spleen, liver, and lymph node, etc. EMH in patients frequently receives less medical attention and is neglected unless a compressive or obstructive hematopoietic mass appears to endanger the patient's life. However, on a biological basis, EMH reflects the alteration of relationships among hematopoietic stem and progenitor cells (HSPCs) and their original and new microenvironments. The ability of hematopoietic stem cells (HSCs) to mobilize from the bone marrow and to accommodate and function in extramedullary tissues is rather complicated and far from our current understanding. Fortunately, many reports from the studies of drugs and genetics using animals have incidentally found EMH to be involved. Thereby, the molecular basis of EMH could further be elucidated from those animals after cross-comparison. A deeper understanding of the extramedullary hematopoietic niche could help expand stem cells in vitro and establish a better treatment in patients for stem cell transplantation.